PENGEMBANGAN KONTEN PEMBELAJARAN BAHASA INDONESIA DI MEDIA SOSIAL: STRATEGI DAN IMPLEMENTASI DIGITAL - Novia Eka Puspita Sari; Kaylacika, Kaylacika (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2025)
This study examines digital strategies and implementation in developing Indonesian language learning content on social media. In this digital era, social media has become an integral part of life, including education, driving the need for updated Indonesian language learning strategies to be more relevant and engaging for learners. Social media offers great potential as an interactive and broad platform for developing Indonesian language learning content, but requires a well-thought-out strategy and appropriate digital implementation for optimal results. The purpose of this article is to fill this research gap by offering a comprehensive strategy and digital implementation for Indonesian language learning content on social media, including exploring various types of content such as infographics, short videos, interactive quizzes, and language challenges to improve grammar comprehension, vocabulary, and language skills (reading, writing, speaking, and listening). Proposed solutions include selecting the right platform, designing engaging visuals and narratives, and evaluating content effectiveness. Thus, this article highlights the creative use of social media features for an immersive and sustainable learning experience, while addressing challenges such as information validity and distraction.